2015
DOI: 10.1007/s00170-015-7323-8
|View full text |Cite
|
Sign up to set email alerts
|

3D FEM simulation of helical milling hole process for titanium alloy Ti-6Al-4V

Abstract: As an emerging hole-machining methodology, helical milling process has become increasingly popular in aeromaterials manufacturing research, especially in areas of aircraft structural parts, dies, and molds manufacturing. Helical milling process is highly demanding due to its complex tool geometry and the progressive material failure on the workpiece. This paper outlines the development of a 3D finite element model for helical milling hole of titanium alloy Ti-6Al-4V using commercial FE code ABAQUS/Explicit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Our FEM model on flat helical milling tool and its associated experimental validation suggested that for helical milling of Ti-6Al-4V, the cutting force required was smaller than that of other traditional drilling processes. This infers a lower stress experienced by the machined surface, less severe tool wear and hence a better surface quality of the borehole and smaller deformation around the borehole [17].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our FEM model on flat helical milling tool and its associated experimental validation suggested that for helical milling of Ti-6Al-4V, the cutting force required was smaller than that of other traditional drilling processes. This infers a lower stress experienced by the machined surface, less severe tool wear and hence a better surface quality of the borehole and smaller deformation around the borehole [17].…”
Section: Discussionmentioning
confidence: 90%
“…Fig. 1 Schematic of the helical milling process [17] Surface roughness (R a ) values of holes produced by different machining processes are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the finite element method (FEM) has played a very important role in the investigation of the cutting process for metal materials. Many researchers have established finite element models to study the cutting process and these models include 2D and 3D models [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Xie et al [9] used the finite element method to study the shear localization phenomena and chip formation in metal cutting process.…”
Section: Introductionmentioning
confidence: 99%
“…Maurel-Pantel et al [13] developed the 3D cutting model to perform the shoulder milling simulation of AISI 304L stainless steel by the software LS-Dynacopy. Ji et al [14] simulated the helical milling hole process of Ti6Al4V alloy by a 3D finite element model with the damage initiation and evolution criterion. Mir et al [15] presented a feasibility study of the potential application of the surface defect machining (SDM) method in the fabrication of silicon and similarly hard and brittle materials using a smooth particle hydrodynamics (SPH) simulation approach.…”
Section: Introductionmentioning
confidence: 99%